Penny Postcard of the Sulfur Mountain Hot Springs, Ventura County, CA - United States Post Office::::::
This penny postcard depicts the entrance of the Sulfur Mountain Hot Springs on the eastern end of the Ojai Valley. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.